Application of input-output analysis in the health care - Maciej Jewczak; Jadwiga Suchecka (Comparative Economic Research. Central and Eastern Europe, 2014)
Usage of the economic analysis in the study of the performance of health care system does not surprise anyone nowadays. Trends that are drawn over the years fluctuate from the technology assessment of health programs - in terms of efficiency, costs or utility for patients, through methods to establishing copayment for health services and the demand for medical services. Much of the interest is devoted to analysis of the shape of the health care system: the amount of contributions to the National Health Fund, the managing the system, both at the micro and macro level, or restructuring. Any method that allows to show dependencies, identify weaknesses/strengths of the health care system is appreciated by health policy makers. The aim of this article is an attempt of the use of models of input-output type in the analysis of the performance of the health care sector in Poland. The construction of input-output model is based on the observed data for the specified, variously defined area - it may concern: country, region, municipality, etc., hence with the appropriate designed database, it may be possible to examine the flow of health benefits - for example, expressed in zlotys. Part of the article is dedicated to theoretical aspects of the input-output models and the problems this usage can cause.
Keywords: 330; input-output models; the health sector; the analysis of flows